2010
DOI: 10.1007/s00296-010-1524-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of malignancy in Japanese patients with rheumatoid arthritis

Abstract: To determine the incidence of malignancy and site-specific malignancies in Japanese patients with rheumatoid arthritis (RA). In a prospective large observational cohort study named IORRA, 7,566 patients with RA were enrolled from April 2001 to April 2005 and were followed up to October 2005. Occurrence of malignancy was originally collected by patient reports of IORRA survey biannually from April 2001 to October 2005, and was confirmed by medical records. Standardized incidence rate (SIR) of the observed-to-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 33 publications
7
68
1
Order By: Relevance
“…Reduced risk of breast cancer was observed in Caucasians patients with RA. These results are consistent with previous reports from Western countries in RA patients [6, 7, 1222, 24]. It has been reported that the epidemiology of malignancy in Japan differed from that in Western countries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Reduced risk of breast cancer was observed in Caucasians patients with RA. These results are consistent with previous reports from Western countries in RA patients [6, 7, 1222, 24]. It has been reported that the epidemiology of malignancy in Japan differed from that in Western countries.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that the epidemiology of malignancy in Japan differed from that in Western countries. In Japanese population, breast cancer became the worst type of tumor followed by uterus and stomach cancers in women [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, about half the patients who developed serious infections within the first year of initiating TCZ treatment and who had subsequently discontinued treatment were older, had longer disease duration, and had more respiratory comorbidities compared with patients who had a presumed lower risk of serious infection and remained in the Malignant lymphoma occurs with a significantly higher incidence in patients with RA compared with the general population 12 . The SIR for malignancies in our study were lower than those reported to date in a large cohort of Japanese patients with RA 13 . The SIR for malignant lymphoma in the current study were not higher than those in biologic-experienced Japanese patients with RA reported by the Japan College of Rheumatology 14 .…”
contrasting
confidence: 54%
“…1 Pitting edema of the hands, synovitis, and failure to grip. (From [7], with permission) 437.1 per 100,000 person-years [36]. In a recent study of malignancy association with PMR in the UK, there was a 69 % increased risk of a cancer diagnosis within the first 6 months after a diagnosis of PMR.…”
Section: Rs3pe Is a Syndrome And Associated With Numerous Disordersmentioning
confidence: 97%